A meshless method for topology optimization of structures under multiple load cases. (June 2020) - Li, Jiao; Guan, Yanjin; Wang, Guangchun; Wang, Guilong; Zhang, Haiming; Lin, Jun
Abstract: This paper focuses on a new topology optimization method for the structures under multiple loading cases. Meshless Smoothed Particle Hydrodynamics (SPH) method is improved to accurately and stably solve solid mechanics. Design variable is chosen as the particle's density, which has the same interpolation scheme as the displacement field. The smoothness of density field is improved and the [0, 1] bounds of density field can be always ensured. The compliances related to each load are calculated by SPH method and are weighted to form the objective function. By using the modified Solid Isotropic Material with Penalization (SIMP) method and Optimality Criteria (OC) method, the densities and material properties of SPH particles are renewed iteratively. Three topology optimization problems are successfully solved and validated by comparing the results to the ones in literature. The mesh-dependency and checker-board phenomenons do not appear, which demonstrates the effectiveness of the proposed SPH algorithm.